2019
DOI: 10.1021/acs.inorgchem.8b03477
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Transformation of Antimetastatic and Cytotoxic Rhodium(III)–Dimethyl Sulfoxide Complexes in Biological Fluids: An XAS Speciation Study

Abstract: Rhodium­(III) anticancer drugs can exert preferential antimetastatic or cytotoxic activities, which are dependent on subtle structural changes. In order to delineate factors affecting the biotransformations and speciation, mer,cis-[RhCl3(S-dmso)2(O-dmso)] (A1) and mer,cis-[RhCl3(S-dmso)2(2N-indazole)] (A2) have been studied by X-ray absorption spectroscopy (XAS). Interactions of these complexes with saline buffer, cell culture media, serum proteins (albumin and apo-transferrin), native and chemically degraded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 102 publications
2
3
0
Order By: Relevance
“…This corresponds to an oxidation state of Rh δ+ based on the partial charge transfer from Rh to S, in agreement with XPS and DRIFTS analyses. The characteristic broad white line around 23240 eV observed in the XANES data was already reported for diverse RhxSy species 36,37 . The corresponding Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectra are plotted in Figure 3e and prove the existence of rhodium sulphides phases.…”
Section: Synthetic Access To Supported Rhodium Sulphide Nanoparticlessupporting
confidence: 72%
“…This corresponds to an oxidation state of Rh δ+ based on the partial charge transfer from Rh to S, in agreement with XPS and DRIFTS analyses. The characteristic broad white line around 23240 eV observed in the XANES data was already reported for diverse RhxSy species 36,37 . The corresponding Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectra are plotted in Figure 3e and prove the existence of rhodium sulphides phases.…”
Section: Synthetic Access To Supported Rhodium Sulphide Nanoparticlessupporting
confidence: 72%
“…This basically corresponds to an oxidation state of Rh δ+ based on the partial charge transfer from Rh to S in rhodium sulphide samples, as already concluded before from XPS and DRIFTS analyses. The characteristic broad white line around 23240 eV observed in the XANES data was already reported for diverse RhXSY species [46][47][48] . The corresponding Fourier transformed extended X-ray absorption fine structure (FT-EXAFS) spectra are plotted in Figure 3e and prove the existence of rhodium sulphides phases.…”
Section: Synthesis and Characterization Of Supported Rhodium Sulphide...supporting
confidence: 70%
“…258,509 In studies by Wardhani et al, the stability of these Ru(II) phosphophores under biologically relevant conditions was validated through XAS (X-ray absorption spectroscopy) at the Ru K-edge, as each element in biological matrix occurs at different energies. 509,[526][527][528][529][530][531][532][533][534][535] XAS of Rubb 7 -TNL in biological media (human serum and cell culture medium) closely resembled that of the free complex and did not change after 24 hr of incubation at 310 K. 509 XAS analysis of the coordination environment of metal complexes in complex biological matrices is a very powerful technique, 509,526,528,533,535 and XAS results indicated that Rubb 7 -TNL maintained its original ligands, and is highly stable to substitution reactions with targets in biological environments. Slight differences were observed in the cell culture medium compared to PBS due to the presence of proteins and the potential binding of Rubb 7 -TNL in specific protein pockets, which resulted in minor outersphere effects.…”
Section: Labelling By Novel Tetranuclear Polypyridylruthenium(ii) Com...mentioning
confidence: 99%